Management Issues with Infection Control during Trauma Resuscitation in the Era of COVID-19: South African Experience. - Hardcastle, Timothy Craig; Hollander, Daniel Den; Ganchi, Feroz; Naidoo, Shanisa; Shangase, Thobekile Nomcebo (Bangladesh Journal of Medical Science, 2021)
Background: This invited short report aims to document the management of trauma and nontrauma ICU patients in one quaternary facility in South Africa during the first two waves of the SARS CoV2 (Covid-19) pandemic in Kwa Zulu-Natal. Content: The setting of the trauma service and the changes made to ensure staff and patient safety are detailed. A brief overview of the clinical experience of caring for both trauma and non-trauma cases is provided along with the management of those cases who were found to be Covid-19 positive. The concerning aspect of increased antibiotic resistance development and the potential roles of antiseptic sanitisers is briefly discussed. Conclusion: Trauma care is essential during the infectious pandemic and there is a risk of increased antibiotic resistance. Doing the basics “right” can prevent staff contamination or adverse patient outcomes. Bangladesh Journal of Medical Science Vol.20(5) 2021 p.72-76